Pengaruh Sosialisasi Perpajakan, Sanksi Perpajakan, Kondisi Keuangan, dan Kesadaran Diri Wajib Pajak Terhadap Kepatuhan Wajib Pajak di Masa Pandemi Covid-19 : (Studi Kasus Pada Wajib Pajak Orang Pribadi Yang Terdaftar Di KPP Pratama Kota Metro) - Sekar Woro Wulandari; Anita Kusuma Dewi; Damayanti Damayanti (Politeknik Negeri Lampung, 2023)
This research aimed to examine the effect of tax socialization, tax sanction, financial condition, and taxpayer’s self-awareness on taxpayers compliance during the pandemic of Covid-19 partially and simultaneously. This research is survey research. The data were collected using the questionnaire method which was directly distributed to the respondents who are individual taxpayers registered in KPP Pratama Metro City (except civil servants and BUMN employees). After all data collected, authors carried out the data test and hypothesis test through SPSS version 21. The result showed that tax socialization didn’t affect the taxpayer’s compliance, while tax sanction, financial condition and taxpayer’s self-awareness affect individual taxpayer’s compliance registered on KPP Pratama Metro City.